A Comprehensive Overview of the Impacting Factors on a Lithium-Ion-Battery’s Overall Efficiency - Simeon Kremzow-Tennie; Tobias Scholz; Friedbert Pautzke; Alexander Popp; Heiko Fechtner; Benedikt Schmuelling (Power Electronics and Drives, 2022)
This comprehensive overview of the impacting factors on lithium-ion-battery’s (LIB) overall efficiency presents the most relevant influencing factors on a battery’s performance. Dissected into their respective short-term and long-term influences, the working principles behind the efficiency influencing factors are presented. With a strong focus on battery characterisation, charge-profiles and battery management systems (BMSs), the authors present results of their own practical research with a detailed literary analysis, allowing a broad coverage of the complex topic. Finally, the authors present a principle model that indicates the interactions between the different involved components of the battery.